شروط ومتطلبـات بنـاء الحكومة الإلكترونية ودورها في دعم مسيرة التنمية في إفريقيا. (El-Wahat Journal for Research and Studies, 2025)
The Great Development Taking Place In The Field Of Information And Communication Technology, Whose Impact Extended To All Aspects Of Public Life, Brought About A Fundamental Change In The Form And Role Of Government Agencies And Their Relations With Each Other And With Citizens, And This Necessitated The Emergence Of The Concept Of E-Government, Which Aims Mainly To Improve The Government’s Relationship With Citizens Of While Facilitating The Communication Process And Providing Them With Electronic Public Services, And From Here It Was Necessary To Refrain From The Idea Of Traditional Government And Move Towards What Is Known As E-Government. As E-Government Is One Of The Most Important And Contemporary Facets Of Information Technology Responsible For Economic Growth And Sustainable Development, But The Experiences Of Countries Differ In This Field, Some Of Them Have Made Great Strides, And Some Are Recording Significant Progress, And Other Countries Are Still In The Early Beginnings On The Path To Establishing E-Government, Through This Research Paper, We Will Try To Evaluate The Readiness Of African Countries To Establish E-Government By Making Comparisons Between These Countries And Knowing The Extent Of Progress In Each Country In The Field Of E-Government And This Focus Of Course On The Conditions And Requirements For Building E-Government, Which Requires Research, Analysis And Devising Basic Indicators In Government Electronic, Which Occupies An Advanced And Leading Position In The Process Of Community Building In Light Of The Large And Accelerating Challenges. From This Standpoint, The Research Attempts To Provide An Intellectual And Scientific Framework To Lay The Foundations Of E-Government, Especially In Africa, And To Present Some Suggestions For Policies And Strategies That Are Put Before The Government Sector And Officials To Establish E-Government. Key Words E-Government, Sustainable Development, Electronic Services, Communication Infrastructure, Human Capital.